Aktualisasi Nilai-Nilai Akhlak Karimah Dalam Perspektif Al-Qur’an - Moh. Akmalis Sholihin; Hasan Afandi; Hendra Setiawan; M. Nasrul Danil Hikam; Musyaffa' Rafiqie (Global Education Journal, 2026)
This study analyzes the concept of Actualization of Noble Moral Values ​​from the Perspective of the Qur'an and its comparison with morality and character education. Akhlaq is understood as a reflection of personality that determines human dignity both as individuals and as members of society. Etymologically, akhlaq (khuluq) is closely related to Khaliq (the Creator) and makhluq (the created), emphasizing the existence of both vertical and horizontal dimensions of relationships. This paper highlights the phenomenon of moral decline in modern behavior that deviates from Qur’anic values, such as backbiting (ghibah), negative suspicion, and conflicts on social media. Through a terminological approach proposed by scholars such as Al-Ghazali, akhlaq is defined as a disposition firmly rooted in the soul from which actions arise spontaneously without requiring deliberate thought. The analysis reveals a fundamental difference in sources of values: akhlaq is grounded in divine revelation that is universal and eternal, whereas morality is based on social consensus and character (budi pekerti) relies on human reason. The internalization of these values is emphasized as the key to achieving both spiritual and worldly well-being.